Ethylenediurea (EDU) inhibits OsORAP1 expression in rice (Oryza sativa L:): Varietal differences in ozone protection efficacy - Rigyan Gupta; Shamsul H. Prodhan; Md. Nazmul Hasan; Shamsun Nahar Begum; Mohammad Hasanuzzaman Rani; Mirza Mofazzal Islam; Md Ashrafuzzaman (PLoS ONE, 2025)
Rising tropospheric ozone concentrations pose a significant threat to crop production in many Asian countries like Bangladesh, necessitating the development of ozone-tolerant rice (Oryza sativa L.) varieties. This study investigates the response of the OsORAP1 allele—an important regulator of the plant’s response to ozone stress, whose expression is associated with ozone-induced damage—in different rice varieties, particularly Kasalath-type and Nipponbare-type, under treatment with ethylenediurea (EDU), a protective antiozonant used in plant research under ambient ozone stress. The experiment, conducted during the 2022 irrigated season, involved growing of 20 rice varieties under a split-plot design with and without 300 ppm EDU treatment, followed by genomic DNA collection at the vegetative stage to differentiate Kasalath-types and Nipponbare-types, and RNA extraction from 10 selected varieties at the flowering stage for gene expression analysis. The research revealed distinct genetic responses between the two types, with Nipponbare-type varieties showing significant increases in OsORAP1 expression and more leaf bronzing score (LBS) without EDU protection. In contrast, Kasalath-type varieties exhibited less pronounced responses due to their inherent tolerance to ozone stress. The effects of EDU on with Kasalath-type varieties responding notably in parameters such as ineffective tillers and straw yield, while Nipponbare-types showed significant changes in unfilled grains and grain yield. Additionally, differences were observed in how EDU treatment influenced reflectance indices parameters, indicating variability in how these varieties mitigate ozone stress. The study underscores the complex interaction between genetic factors, environmental conditions, and treatment in shaping the response of rice varieties to EDU, and suggests future research to further explore the genetic mechanisms, particularly the role of OsORAP1, that contribute to these differential responses.